Structural stability of anhydrous proton conducting SrZr0.9Er0.1O3−δ perovskite ceramic vs. protonation/deprotonation cycling: Neutron diffraction and Raman studies. (August 2015) - Slodczyk, Aneta; Colomban, Philippe; Upasen, Settakorn; Grasset, Frédéric; André, Gilles
Abstract: Long-term chemical and structural stability of an ion conducting ceramic is one of the main criteria for its selection as an electrolytic membrane in energy plant devices. Consequently, medium density SrZr0.9 Er0.1 O3-δ (SZE) anhydrous proton conducting ceramic – a potential electrolyte of SOFC/PCFC, was analysed by neutron diffraction between room temperature and 900 °C. After the first heating/cooling cycle, the ceramic pieces were exposed to water vapour pressure in an autoclave (500 °C, 40 bar, 7 days) in order to incorporate protonic species; the protonated compound was then again analysed by neutron diffraction. This procedure was repeated two times. At each step, the sample was also controlled by TGA and Raman spectroscopy. These studies allow the first comprehensive comparison of structural and chemical stability during the protonation/deprotonation cycling. The results reveal good structural stability, although an irreversible small contraction of the unit-cell volume and local structure modifications near Zr/ErO5 [] octahedra are detected after the first protonation. After the second protonation easy ceramic crumbling under a stress is observed because of the presence of secondary phases (SrCO3, Sr(OH)2 ) well detected by Raman scattering and TGA. The role of crystallographic purity, substituting element and residual porosity in the proton conducting perovskite electrolyte stability is discussed. Graphical abstract: Highlights: Neutron diffraction, TGA and Raman study of SrZr0.9 Er0.1 O3-δ proton conductor. First study of structural stability during protonation/deprotonation cycling. SrZr0.9 Er0.1 O3−δ shows high structural stability vs. protonation/deprotonation cycles. First protonation is crucial for long-term structural/chemical stability. Grain boundary 2nd phases leads to loss of mechanical properties.